Effect of Purified l-Hydroxyphenazine Pigment on Lymphocytes Viability Against Experimental Secondary Hydatidosis - Zaman Ibrahim (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To find out the effect of l-hydroxyphenazine (1-HP) on viability of T-lymphocytes and the reflects of thiseffect on experimental hyadatidosis on hydatid cyst protoscoleces infectivity in vivo.Methodology: Four groups of white male /ه/mice were experimentally infected with four concentrations of (1-HP)with challenge dose of 2000 protoscoleces /1 ml with negative (9.8.5) and positive (P.H.A) control groups.Results: It has been found that the higher concentrations (75,100) 1101/111 of the (1-HP) causes significantdecrement in the lymphocytes viability in comparison with negative and positive control groups. (060.01).Recommendations: The study recommended using concentrations lower than 25 pmole Iml which may be able toactivate the T-lymphocytes against experimental hydatidosis.